Structure and elicitor or u.v.-light-stimulated expression of two 4-coumarate:CoA ligase genes in parsley - Douglas, Carl (1987)
We have isolated genomic clones encoding 4-coumarate:CoA ligase (4CL), a key enzyme of general phenylpropanoid metabolism, and have analysed the structure and regulation of the genes contained on these clones. Restriction enzyme and sequence analysis indicated that two distinct 4CL genes, Pc4CL-1 and Pc4CL-2, are represented on the clones and that additional 4CL genes are not present in parsley. Two lines of evidence suggest that each gene is transcriptionally activated by both elicitor and u.v. irradiation: cDNA clones corresponding to each gene were found in cDNA libraries made with RNA from both elicitor-treated and u.v-irradiated cells, and run-off transcripts homologous to a Pc4CL-2-specific intron probe were induced by both treatments. This induction was about half of the induction measured using probes homologous to both genes. The transcription initiation sites of both genes were determined. Comparison of the nucleotide sequences of the two genes 5' to these sites showed that they are highly homologous for several hundred base pairs and that they contain features potentially involved in regulation by elicitor and u.v. irradiation.